Mangrove rehabilitation on Carey Island, Malaysia: an evaluation of replanting techniques and sediment properties. Issue 4 (21st April 2017) - Bakrin Sofawi, Ahmad; Rozainah, Mohamad Zakaria; Normaniza, Osman; Roslan, Hashim
ABSTRACT: We assess the suitability of conventional replanting techniques of Rhizophora mucronata and the relationship with soil properties, and compare the differences between rehabilitation and non-rehabilitation sites, on Carey Island, Malaysia. The average survival rate of planted seedlings at the rehabilitation site was 46% in the first six months, gradually reducing to complete mortality after one year, while no survival was recorded at the non-rehabilitation site from the beginning. Over the short period, survival of the clumped planting technique yielded the highest survival rate (75%) compared with random (33%) and uniform (30%) techniques; with a height increment of 2.48 ± 1.87 cm/month, diameter increment of 0.49 ± 0.81 mm/month, leaf increment of 2.05 ± 2.80 and chlorophyll content of 32.08 ± 5.80 SPAD (= Soil Plant Analysis Development values). Fifteen new recruits of Avicennia spp. with a 60% survival rate were recorded in the rehabilitation site at the end of the study. Soil texture changed significantly at the rehabilitation site from sandy loam (clay, 2.85%; silt 33.93%; sand, 63.21%) to silty loam (clay, 1.88%; silt 60.74%; sand, 37.38%). Soil nutrients: carbon (C), nitrogen (N) and potassium (K) were significantly higher in the top 40 cm at the rehabilitation site while phosphorus (P) was lower. We argue that nutrient differences between the rehabilitation and non-rehabilitation sites affected the health of both planted and wild seedlings and ultimately the success of the rehabilitation effort. As the soil condition improves at the rehabilitation site, natural recruitment would be the best available option in this restoration process.